Selected writings on Marxism - Hall, Stuart, 1932-2014 (Hall, Stuart, 1932-2014. Works. 2016., 2021)
"This collection of Stuart Hall's key writings on Marxism surveys the formative questions central to his interpretations of and investments in Marxist theory and practice."--